The Application of Ethnomathematics in Numeracy Literacy Perspective: A Literature Review - Munthahana, Jayanti; Budiarto, Mega Teguh; Wintarti, Atik (Indonesian Journal of Science and Mathematics Education, 2023)
Numerical literacy skills in Indonesia remain inadequate, despite these skills being critical for problem-solving. This study aims to review recent ethnomathematics research in the context of numeracy literacy. The design of this study was a literature review using a qualitative descriptive analysis method, with fifteen accredited Sinta, Scopus, and international proceedings related to the use of ethnomathematics in the context of numeracy literacy. The data collection technique employed was a literature study. The results of this study show that the ethnomathematics context in Indonesia can be determined through indicators of mathematical activity and sub-elements in a social-cultural system. These concepts include numbers, geometry, measurement, algebra, data, and uncertainty. The results of numeracy literacy were found to vary in various studies. Thus, applying ethnomathematics can be an alternative to classroom learning to measure students' numeracy literacy abilities. This measurement can be used as a suggestion for further research.